Penyelenggaraan Program Majalah Dinding Sebagai Solusi Meningkatkan Minat Membaca Dan Kreatifitas Menulis Pada Anak Di Masa Pandemi Covid-19 Di TPQ Mambaul Jannah Desa Sukosari Kec. Kasembon Kab. Malang - Muhammad Bahrun Nafi’in; Soni Amrulloh (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Wall magazines are one of the simplest types of mass communication media. It is called wall magazine because the basic principle of the magazine feels dominant in it, while the presentation is usually displayed on the wall or the like. The principle of the magazine is reflected through its presentation, whether in the form of writing, images, or a combination of the two. The implementation of the wall magazine program as a solution to increase reading interest and writing creativity in children during the covid-19 pandemic at TPQ Manbaul Jannah Dusun Mangir Sukosari Kec. Kasembon Kab. Malang. Wall magazine activities that delight students with media and simple ways that can be developed in teaching-learning activities as well as help the development of creativity. Wall magazines have a fairly high role in the efforts of coaching and student formation, in aspects of knowledge, abilities, interests and talents. And as one of the facilities of student activities physically and factually and has a number of functions, namely informative, communicative, recreative, creative. The community is very supportive with the wall magazine program because many parents are concerned that their children are more active in playing hand phones to find entertainment and games, rather than to do schoolwork.